2020
DOI: 10.1186/s40816-020-00213-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-rich Tamarindus indica L. leaf extract reduced high-fat diet-induced obesity in rat through modulation of gene expression

Abstract: Background Different parts of the medicinal plant Tamarindus indica L. are full of phytochemicals that are able to reduce elevated blood pressure, blood sugar and lipids. These pharmacological effects are due to the presence of antioxidant type compounds in those parts of the plant. This study was aimed to explore the molecular mechanism of anti-obesity effects of ethanolic extract of T. indica L. leaves (TILE) through the evaluation of biochemical parameters and gene expression analysis in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
2
0
3
Order By: Relevance
“…It has been showed that it is a medical status with fat overproduction associated with a usual oxidative stress and low intensity inflammation that lead to systemic alterations in the body. 41,42 For this, it was important to figure out the antioxidant activity in the obesity-related study because of the strong relationship between obesity and oxidative stress. In this context, the in vitro radical-scavenging capabilities show that AUAE and CMAE exhibit potent antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that it is a medical status with fat overproduction associated with a usual oxidative stress and low intensity inflammation that lead to systemic alterations in the body. 41,42 For this, it was important to figure out the antioxidant activity in the obesity-related study because of the strong relationship between obesity and oxidative stress. In this context, the in vitro radical-scavenging capabilities show that AUAE and CMAE exhibit potent antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Reseptor PPARγ banyak diekspresikan pada jaringan white adipose tissue (WAT) dan brown adipose tissue (BAT). Sehingga PPARℽ merupakan salah satu penanda WAT selain C/EBPα dan FABP4 yang berkaitan dengan metabolisme hingga biosintesis asam lemak, Trigliserida, kolesterol serta pengaturan reseptor insulin [41].…”
Section: Sindrom Metabolikunclassified
“…SREBP-1 juga ditemukan sebagai regulator transkripsi penting yang terlibat dalam adipogenesis. Interaksi pengaturan antara SREBP-1 dan PPARγ/C/EBPα dapat mengkoordinasikan diferensiasi preadiposit penuh menjadi adiposit, serta menginduksi ekspresi gen FABP4, ACC, FAS, HMG-CoA reduktase dan LPL yang terkait dengan metabolisme sampai biosintesis asam lemak, TG, kolesterol secara de novo serta pengaturan reseptor insulin [15], [18]. Secara bersama-sama, penghambatan adipogenesis dengan memodulasi aksi bersama gen spesifik adiposit (PPARγ, C/EBPα, SREBP-1, FAS, FABP4, dan LPL) diharapkan memberikan strategi kunci untuk mengendalikan obesitas [16], [19].…”
Section: Pparℽunclassified
“…T. indica menurunkan ekspresi gen PPARℽ, C/EBPα, dan SREBP-1c sama seperti T. fuciformis [47]. Selain itu senyawa polifenol yang terdapat pada tanaman ini mampu bekerja sebagai antioksidan selain mampu menekan akumulasi lipid dan peningkatan berat badan [18]. B. scorzenifolium mampu menurunkan ekspresi FASN, SREBP-1c sedangkan meningkatkan ATGL pada hewan uji.…”
Section: Mekanisme Kerjaunclassified